DETERMINASI PERTUMBUHAN EKONOMI DI NEGARA ASEAN-6 - Aprillia ,; Dini Hariyanti (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2014)
Economic growth is an indicator that is important in analyzing the economics development in a country. Economics growth shows how economic activities will generate additional income for a society in a certain period.This research aims to investigate what factors that determine economics growth in ASEAN, during 1995-2012. ASEAN-6 (Indonesia, Malaysia, Singapura, Thailand, Philipina, dan Vietnam) are chosen to be the object of this research. This research is divided into two main parts. The first part is discussed about the determinant factors of economics growth in ASEAN-6 generally, and the second part is the partial analysis in each country, so it is expected that each country could formulate the appropriate policy according to each condition. By using panel data analysis and STATA 11 as the software, it is seen that generally, factors determine economic growth in ASEAN-6 are the growth of GDP, trade openness, gross fixed capital formation, and inflation rate. From partial analysis result, country with the highest economics growth is Vietnam, followed by Indonesia, Malaysia, Singapora, Philippine, and the last is Thailand.